Contingency, Free Will, and Particular Providence - Torrijos Castrillejo, David (Religions, 2021)
The results from contemporary science, especially the theory of evolution and quantum physics, seem to favor process theology. Moreover, the evil committed by free will leads some theologians to reduce divine action in order to prevent God from being responsible for evil. Thus, among those who defend a particular providence, Molinism finds many followers. This article first argues that contemporary science does not constrain us to deny particular providence. Second, it criticizes the implicitly deterministic character of Molinism. Thirdly, a Thomistic solution is proposed as an alternative which, by means of a different metaphysical approach to cosmic contingency and freedom of will, defends particular providence without reducing divine activity except in personal sins.